2010
DOI: 10.1158/0008-5472.can-09-4676
|View full text |Cite|
|
Sign up to set email alerts
|

Oncogenic Ras Promotes Reovirus Spread by Suppressing IFN-β Production through Negative Regulation of RIG-I Signaling

Abstract: Reovirus is the first naturally occurring human virus reported to exploit activated Ras signaling in the host cell for infection, and is currently undergoing clinical trials as a cancer therapeutic. Recent evidence suggests that Ras transformation promotes three reoviral replication steps during the first round of infection: uncoating of the incoming virion, generation of progeny viruses with enhanced infectivity, and virus release through enhanced apoptosis. Whether oncogenic Ras also enhances reovirus spread… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 27 publications
4
111
0
Order By: Relevance
“…However, in RAS-negative fibroblasts, all reovirus subtypes did not show oncolytic activity. These observations are in accordance with previous studies (5,10,11,(14)(15)(16).…”
Section: Discussionsupporting
confidence: 94%
“…However, in RAS-negative fibroblasts, all reovirus subtypes did not show oncolytic activity. These observations are in accordance with previous studies (5,10,11,(14)(15)(16).…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with prior reports, reovirus exposure induces an IFN-b response (Hamamdzic et al, 2001;Holm et al, 2007;Steele et al, 2011). While IFN production has been reported to decrease viral spread and efficacy, IFNs have also been shown to elicit anti-tumor effects via inhibition of angiogenesis and stimulation of apoptosis (Sidky and Borden, 1987;Taylor et al, 2008;Shmulevitz et al, 2010). To investigate whether IFN-b contributes to Reolysin-mediated apoptosis, we blocked its activity with neutralizing antibody.…”
Section: Resultssupporting
confidence: 70%
“…Our initial gene expression profiling experiment demonstrated that Reolysin treatment induced a strong IFN-b response. This is not surprising given that previous studies have demonstrated that this antiviral response may limit reovirus replication in nontransformed cells (Rudd and Lemay, 2005;Shmulevitz et al, 2010). However, it is also possible that IFN stimulation may contribute to Reolysin's anti-tumor activity (Taylor et al, 2008).…”
Section: Discussionmentioning
confidence: 79%
“…Mammalian reovirus (type 3 Dearing) and RSV (serotype A, Long strain) were propagated, purified, and UV‐inactivated as previously described 28, 31, 32. UV inactivation was confirmed by standard plaque assay and flow cytometric analysis of virus treated cells.…”
Section: Methodsmentioning
confidence: 99%